Analysis of the Influence of Discipline, Competence, and Work Motivation on the Performance of Police Personnel - Hakim, Lukmanul; Riki Kurniawan; Ma'ruf, M. Hasan Ma'ruf (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of work discipline, work competence, and work motivation on the performance of Pringsewu Police personnel. Police performance is an important aspect in realizing professional, modern, and reliable public services. However, empirical data shows that the performance of the Pringsewu Police during the 2021-2024 period has fluctuated with a downward trend, accompanied by an increase in disciplinary violations. This study uses a quantitative approach with a survey method. The research population is all members of the Pringsewu Police totaling 410 personnel, with a sample of 201 respondents determined through proportional random sampling. Data collection was carried out by Likert scale questionnaire, while data analysis used multiple linear regression with tests of validity, reliability, and classical assumptions. The results of the study show that work discipline has a significant effect on personnel performance. Work competence makes a positive contribution to the effectiveness of task implementation, while work motivation has a significant effect on increasing personnel dedication and responsibility. Simultaneously, the three variables have a significant effect on the performance of the Pringsewu Police. These findings confirm that human resource management based on discipline, competence, and motivation is an important determinant in improving police performance. Keywords: Work discipline; Competence; Motivation; Performance; Police